Legal Review of the Criminal Act of Embezzlement in Office - Ilham Siahaan (Outline Publisher, 2025)
This study aims to analyze the basis for the judge's considerations in applying articles in the case of embezzlement in office at the Medan District Court, decision number 789 / Pid.B / 2024 / Pn.Mdn. The main problems studied include (1) how the regulation of the crime of embezzlement and the distinction between Article 372 and Article 374 of the Criminal Code; and (2) how the judge's considerations in proving the elements of the offense in the a quo case. The study uses a normative juridical method with a statute approach and a case study, through a review of relevant doctrines, literature, and trial files. The results of the analysis show that the Panel confirms the fulfillment of the elements of embezzlement in office based on Article 374 of the Criminal Code; with an alternative indictment construction that places Article 372 of the Criminal Code as a subsidiary; because the goods are in the defendant's possession due to his employment/work relationship; and the defendant's position as a collector; with a loss value of around Rp. 2,500,000; involving 35 people. This consideration is in line with the doctrine that Article 374 of the Criminal Code is a lex specialis of Article 372 of the Criminal Code when control of goods arises due to position/work/wages, so that the application of Article 374 is appropriate in this case. The academic implication emphasizes the importance of proving the employment relationship as a determinant of the qualification of the crime, while the practical implication encourages stakeholders (companies/cooperatives) to strengthen the SOP for financial management and deposits to prevent embezzlement in office.